KNOWLEDGE, PRACTICES AND FACTORS INFLUENCING REPORTING OF NOTIFIABLE DISEASES AMONG HEALTH WORKERS IN TWO SELECTED RURAL AND URBAN LOCAL GOVERNMENT AREAS OF OYO STATE, NIGERIA (2014)
Reporting of notifiable diseases is essential for control and prevention of outbreak of diseases. In Nigeria, reporting of Notifiable Diseases by health workers has not been adequately documented. This study was conducted to assess health workers knowledge, practices, and factors influencing disease reporting in urban and rural communities in Oyo State, Nigeria. A cross-sectional survey was carried out among the 210 health workers who were responsible for disease reporting at their health facilities. The 33 local government Areas (LGA) of Oyo State were stratified into rural and urban, out of which one rural (Afijio LGA) and one urban (Ibadan North LGA), were randomly selected. All the health facilities in Afijio (39) and Ibadan North (171) were included in the study. One respondent at each health facility (focal person) was then selected and interviewed. A semi-structured, self- administered questionnaire was used to obtain information on knowledge, practices, pattern and factors affecting reporting. The list of diseases included: immediate, routine, international and occupationally notifiable diseases. Knowledge was assessed on a scale of 50 points with score ≥30 as good. Data were analyzed using descriptive statistics; Chi square, t-test and linear regression. Community Health Officers (30.1%), Nurses (26.0%) and Physicians (16.3%), constituted the majority of the respondents. Seventy-two percent (rural- 14.8% and urban- 57.1%) were aware of the existence of disease notification system while 26.5% knew the current strategy for reporting. Mean knowledge score for notifiable diseases among respondents was 27.6±8.4 with group means for rural and urban being 32.0±8.6 and 26.7±8.2 (p<0.001) respectively. About eleven percent (11.2%) of the respondents had good knowledge of the notifiable diseases. Majority (82.8%) of the respondents forwarded their routine health facilities reports to their respective LGA while 17.1% sent theirs to the Ministry of Health. Fifty-six percent of respondents sent reports through their staff while the rest had their facilities report collected by staff from State Ministry of Health and LGA. Main reasons for non-reporting included: lack of training on reporting (84.0%), absence of legal enforcement (58.0%), ignorance of reporting requirements (50.0%) lack of supervision (48.0%) and lack of reporting forms and telephone facilities (38.0%). Health workers that were aware of notification system were five times likely to comply with reporting than those that were not aware. (OR=5.0, 95% C.I = 1.5-17.5). Reporting of notifiable diseases was poor among the health workers at the Local Government level in Oyo State. Lack of training on reporting, absence on legal enforcement and ignorance on reporting requirements were major influencing factors. Regular training, effective supervision and logistic support to all notifiable diseases reporting health workers are recommended.